Role of Jalokaavacharana in the Management of Varicose Veins (Sirajgranthi)- A Case Study - Kazi, Wasim; Patel, Jigna; Sharma, Varsha; Panchal, Sonal (Asian Journal of Pharmaceutical Research and Development, 2023)
When a vein becomes dilated, elongated and tortuous, the veins is said varicose. The common sight of varicosity are superficial venous system of lower limb effecting either long or short saphenous veins, oesophageal varices, varicosity of haemorrhoidal veins, varicosity of spermatic veins. Generally varicose veins are compared with sirajgranthi according to Ayurveda. Acharya Sushruta had described various types of granthi and its various treatment modalities among them jalaukaavacharana is one of them. Sushruta had given special chapter related to jalauka in which he had described the types, nomenclature, specific qualities of each types of jalauka, their method to apply and detach and how to do vamana of jalauka. Acharya charak also described jalauka as best amongst all anushashtras. Jalaukapossesessheet guna in nature and on the basis of sign and symptoms varicose veins can be correlated with sirajgranthi. In this case study a 36- year old woman of bilateral varicose veins was treated successfully and found symptomatic relief.